2017
DOI: 10.1021/acs.jafc.7b00934
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction in the IgE-Binding Ability of β-Lactoglobulin by Dynamic High-Pressure Microfluidization Coupled with Glycation Treatment Revealed by High-Resolution Mass Spectrometry

Abstract: Our previous study indicated that pretreatment by dynamic high-pressure microfluidization (DHPM) and glycation with galactose was a promising method for decreasing the immunoglobulin E (IgE)-binding ability of β-lactoglobulin (β-LG). In this work, the conformational alteration of β-LG subjected to DHPM and glycation treatment was investigated in relation to IgE-binding ability by orbitrap mass spectrometry. After DHPM pretreatment, lower IgE-binding ability of glycated β-LG was observed with increasing pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…According to Chen et al (2017), DHPM treatment could improve the glycation level, by forming more glycation sites via conformational changes of the protein.…”
Section: Changes In Molecular Weightmentioning
confidence: 99%
“…According to Chen et al (2017), DHPM treatment could improve the glycation level, by forming more glycation sites via conformational changes of the protein.…”
Section: Changes In Molecular Weightmentioning
confidence: 99%
“…Previous studies reported that the starches with high‐amylose‐lipid complexes had less chance to swell and gelatinize than normal and waxy starch (Wang et al, ). Researchers agreed that the delay in swelling and gelatinization was due to the emulsifier complexation between amylose and lipids, which could prevent the transport of water into the granules and delay both the release of soluble components and the deformation and collapse of starch granules (Keetels, Van Vliet, Jurgens, & Walstra, ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain starch with beneficial properties, a number of studies into modified starch are increasing in extent year by year. Some new methods are more and more paid attention to the modification of starch, such as high‐pressure processing (HPP) (Cappa, Barbosa‐Cánovas, Lucisano, & Mariotti, ), high‐pressure homogenization (HPH) (Chen, Zeng et al, ; Le Thanh‐Blicharz, Lewandowicz, Błaszczak, & Prochaska, ), irradiation (Dar et al, ), enzymatic hydrolysis, and blending with other food materials (Alamri, Mohamed, & Hussain, ), as well as kinds of crosslinking and grafting methods for specific applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations